ANALISIS ALAT PERAGA MOTOR BENSIN SATU SILINDER 115 CC FUEL INJECTION - Sisranto -; Riri Sadiana (Jurnal Ilmiah Teknik Mesin, 2018)
The use of injection systems in the trainer tool system as a means of learning is one of the goodlearning methods to determine the components, functions and ways of working, thus it will bevery easy for us to understand without having to use the motorcycle directly. For this purpose atriner with components including the ECU (Engine Control Unit), throttle body, injector, fuelpump, rotor, stator, ignition coil, dimmer, main switch and spark plug are made. A trainer toolis said to be feasible if each component works well. Because a trainer tool must be inaccordance with the condition of a work object that the trainer has made. For this reason,analysis and research are needed on the performance of the electronic control unit, the loadingangle and the effect of the throttle body angle on the fuel spraying on the electric fuel injectionnozzle, at a motor speed of 1000-1500 rpm. The results of the design analysis of this trainer toolare when the throttle opening angle is 15o, 24o, 31o, 40o, 55o and 97o with a speed of 1500rpm to reach 3ml gasoline volume, the time taken is 308 s, at an angle of 15o. 171.6 s, at anangle of 24o. 147.4 s at an angle of 31o. 137,867 s, at an angle of 40o. 129.8 s, at an angle of55o. and 111,467 s, at 97o angle. Inversely proportional to the opening of the throttle bodyangle, the smaller the throttle body angle opening, the longer it takes the nozzle when sprayingfuel.